Cost Effectivie Analysis (CEA) Pengobatan Tunggal dan Kombinasi pada Pasien Tuberkulosis Paru di RSUD dr. La Palaloi Kabupaten Maros - Ira Widya Sari; Yani Pratiwi; Irfan Kurniawan; A.Aulia Salsabila (Universitas Muhammadiyah Manado, 2025)
TB treatment requires long-term therapy using anti-tuberculosis drugs (OTAs), either singly or in combination. The use of combination therapy is considered more effective in preventing drug resistance and increasing treatment success. However, the choice of therapy method is also influenced by economic considerations, considering the continuing increase in health care costs. Therefore, a pharmacoeconomic analysis is needed, specifically a Cost Effectiveness Analysis (CEA) to compare the costs and effectiveness of two treatment alternatives, namely single OAT therapy and combination therapy. Cost Effectiveness Analysis (CEA) is a type of pharmacoeconomic analysis in which all costs are compared with the effects of two or more treatment options. Single OAT treatment is a medical action undertaken by tuberculosis patients, while combination treatment is a treatment method consisting of two or more drugs or treatment techniques used simultaneously to increase treatment effectiveness, reduce the risk of resistance, or improve clinical outcomes. The research method is a descriptive non-experimental, the data studied are retrospective using secondary data from patient medical records. The results showed that treatment of pulmonary tuberculosis using combination therapy (rifampicin and isoniazid) is more cost-effective with an ACER value of Rp132. 182 compared to single therapy (ethambutol) with an ACER value of Rp. 170,536 and an ICER value of combination and single therapy of Rp. 119,857.